Microbiology fundamentals a clinical approach - Cowan, M. Kelly; Smith, Heidi; Lusk, Jennifer (McGraw Hill LLC, 2022)
"Welcome! I am so glad you are here. I am very excited for you to try this book. I wrote it after years of frustration, teaching from books that didn't focus on the right things that my students needed. My students (and, I think, you) need a solid but not overwhelming introduction to microbiology and infectious diseases. I asked myself: What are the major concepts I want my students to remember five years from now? And then I worked backward from there, making sure everything pointed to the big picture. While this book has enough detail to give you context, there is not so much detail that you will lose sight of the major principles. Biological processes are described right next to the illustrations that illustrate them. The format is easier to read than most books, because there is only one column of text on a page and wider margins. The margins gave me space to add interesting illustrations and clinical content. A working nurse, Jennifer Lusk, brings her experience to life on the pages and shows you how this information will mat ter to you when you are working as a health care provider. We have interesting and up-to-the-moment Case Files, Medical Moments, Microbiome selections, and NCLEX ® questions in every chapter. My coauthor, Heidi Smith, has brought so much to the book and online material. I don't think you'll find a bet ter online set of learning tools anywhere. I really wanted this to be a different kind of book. I've started using it in my own classes and my students love it! Well, maybe they have to say that, but I hope you truly do enjoy it and find it to be a refreshing kind of science book."--Provided by publisher.